Comparative Study of Glyceryl Behenate or Polyoxyethylene 40 Stearate-Based Lipid Carriers for Trans-Resveratrol Delivery: Development, Characterization and Evaluation of the In Vitro Tyrosinase Inhibition - Fachinetti, Naiara [UNESP]; Rigon, Roberta Balansin [UNESP]; Eloy, Josimar O. [UNESP]; Sato, Mariana Rillo [UNESP]; dos Santos, Karen Cristina [UNESP]; Chorilli, Marlus [UNESP] (Springer Nature, 2018)
Trans-resveratrol (RSV) is a natural compound with several properties, such as the ability to inhibit the tyrosinase enzyme, with potential application as a skin-lightning agent and for the treatment of skin disorders associated with hyperpigmentation and melanogenesis. However, the drug faces several drawbacks which altogether limit its therapeutic application. Thus, drug loading into nanocarriers emerge as an alternative to circumvent these problems. Herein, nanostructured lipid carriers (NLCs) have been employed for RSV encapsulation, with comparison of two different lipids, glyceryl behenate (more hydrophobic), and polyoxyethylene 40 (PEG 40) stearate. PEG 40 stearate-containing NLCs presented smaller particle size and polydispersity compared with glyceryl behenate, attributed to better emulsification and nanoparticle formation, resulting in higher RSV encapsulation efficiency. Drug was loaded in both carriers as a molecular dispersion. Furthermore, the formulations had very low RSV release, which occurred due to the crystallinity degree of lipid matrix, in accordance with the DSC data. Moreover, RSV cytotoxicity against L-929 cells was not increased when loaded into nanocarriers. Interestingly, RSV-loaded formulation prepared with PEG-40 stearate resulted on greater tyrosinase inhibition than RSV solution and formulation containing glyceryl behenate, equivalent to 1.31 and 1.83 times higher, respectively, demonstrating that the incorporation of RSV into NLC allowed an enhanced tyrosinase inhibitory activity. Overall, the results obtained herein evidence potential for future in vivo evaluation of RSV-loaded NLCs.
Keywords: glyceryl behenate; nanostructured lipids carriers; polyoxyethylene 40 stearate; trans-resveratrol; tyrosinase